ANÁLISE DE PESQUISAS SOBRE A PARTICIPAÇÃO SOCIAL NA PRODUÇÃO DE HABITAÇÃO RURAL - Werle, Fhelippe; Yuba, Andrea (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Rural housing production in Brazil is like as a minor issue when compared to urban production. It is not properly developed and it is both, under and misaddressed by public policies. Even with National Rural Housing Program (PNHR), the rules that should ensure the participation of beneficiaries in the housing production, to make them suitable for their way of life and their needs are not clear yet. This fact enables the autonomy and arbitrariness of those responsible for the public policies implementation, generating inadequate and standardized housing. This paper focus on social participation and aims to characterize participatory strategies adopted during the process of rural social housing production. Furthermore, it analyzes the outcomes of performed result of researches that used the research-action as a method in some rural communities. Based on this literature review it is possible to identify strategies, challenges, conflicts, and results in the different stages of such process.